2003
DOI: 10.1074/jbc.m212492200
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Regulation of Bacteriophage λ pR Promoter Activity by Escherichia coli DnaA Protein

Abstract: Apart from its function as an initiator of DNA replication, the Escherichia coli DnaA protein is also a specific transcription factor. It activates and represses a number of promoters. However, mechanisms of transcription stimulation by DnaA remained unknown. Bacteriophage p R promoter is one of the promoters activated by DnaA. It was reported previously that DnaA binds downstream of the p R promoter and perhaps interacts with the RNA polymerase ␤ subunit. Here we demonstrate that DnaA positively regulates tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…There are examples in E. coli where one site with one mismatch and another more degenerate site are sufficient for DnaA-dependent regulation. Additionally, some genes controlled by DnaA have binding sites downstream of the promoter regions, sometimes within an ORF (47,48). These cases would have been missed by our analysis.…”
Section: Discussionmentioning
confidence: 75%
“…There are examples in E. coli where one site with one mismatch and another more degenerate site are sufficient for DnaA-dependent regulation. Additionally, some genes controlled by DnaA have binding sites downstream of the promoter regions, sometimes within an ORF (47,48). These cases would have been missed by our analysis.…”
Section: Discussionmentioning
confidence: 75%
“…The mechanism of this phenomenon remains to be elucidated; nevertheless, it is worth noting that SeqA binds to a region of the l p R promoter and regulates its activity (S omiń ska et al, 2001), and that a decrease in the abundance of the stable O protein fraction is also observed in cells bearing a derivative of l plasmid (pTCl2) in which p R is replaced by another promoter (p tet ) (HermanAntosiewicz et al, 1998a) [the activity of the p tet promoter has been demonstrated to be SeqA independent (S omiń ska et al, 2001)]. Moreover, another regulator of p R activity, the DnaA protein (Szalewska-Pa asz et al, 1998;Glinkowska et al, 2003), has also been suggested to be a factor that influences the stability of the l replication complex (Herman-Antosiewicz et al, 1998a), and an interplay between DnaA and SeqA at the p R promoter region has been clearly demonstrated (S omiń ska et al, 2003b). In this light, seqA dysfunction-mediated suppression of the effects of certain dnaA alleles on the transformation of E. coli cells with l plasmids, demonstrated previously (Glinkowska et al, 2001), and on the directionality of l plasmid replication, suggested in this report, may be important to understand the regulation of l DNA replication initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of studies of the possible role of SeqA in the regulation of replication initiated from origins different from oriC include relatively preliminary observations only, namely the demonstration of the binding of this protein to bacteriophage P1 ori (Brendler et al, 1995), and the findings that the copy number of plasmids derived from bacteriophage l is decreased in a seqA mutant host (S omiń ska et al, 2001) and that the DseqA mutation can suppress incompatibility between l plasmids and certain dnaA(ts) mutants (S omiń ska et al, 2003b;Glinkowska et al, 2003). Here, we investigated the role of SeqA in the regulation of l DNA replication in more detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few transcription activator proteins have been shown to bind downstream of the transcription start site, but little is known concerning their mechanism of activation (32)(33)(34). In the case of regulation of bacteriophage lambda pR promoter activity by DnaA, the location of the binding site downstream of the transcription start site allows a direct interaction between DnaA and the RNA polymerase ␤ subunit (32). Weak binding of DnaA to DNA may contribute to removal of this activator after transcription initiation (32).…”
Section: Discussionmentioning
confidence: 99%